Long-term outcomes of drug-coated balloon treatment of calcified coronary artery lesions: a multicenter, retrospective, propensity matching study - Shan, Yingguang; Lu, Wenjie; Han, Zhanying; Pan, Sancong; Li, Xiangbing; Wang, Xi; Pan, Liang; Wang, Xule; Zheng, Xiaolin; Li, Ran; Zhou, Yanjun; Qin, Peng; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Coronary artery calcification (CAC) is associated with high rates of restenosis and adverse clinical events after percutaneous coronary intervention (PCI) with drug-eluting stents (DES). Objectives: The aim of this study was to evaluate the long-term clinical outcomes of drug-coated balloon (DCB)-only treatment for de novo lesions with and without CAC. Methods: Patients with de novo coronary disease treated with the DCB-only strategy were retrospectively enrolled from three centers and categorized into a CAC group and a non-CAC group. The primary endpoint was the target lesion failure (TLF) rate during the 3-year follow-up. Secondary endpoints included the occurrence of major adverse cardiac events (MACEs), target lesion revascularization (TLR), cardiac death, myocardial infarction (MI) and any revascularization. Propensity score matching (PSM) was performed to assemble a cohort of patients with similar baseline characteristics. Results: A total of 1263 patients with 1392 lesions were included, and 243 patients were included in each group after PSM. Compared with the non-CAC group, the incidence rates of TLF (9.52% vs. 4.94%, odds ratio [OR]: 2.080; 95% confidence interval [CI]: 1.083 to 3.998, P = 0.034) and TLR (7.41% vs. 2.88%, OR: 2.642; 95% CI: 1.206 to 5.787, P = 0.020) in the CAC group were higher. The incidence rates of MACE (12.35% vs. 7.82%, OR: 1.665; 95% CI: 0.951 to 2.916, P = 0.079), cardiac death (2.06% vs. 2.06%, OR: 0.995; 95% CI: 0.288 to 3.436, P = 0.993), MI (1.23% vs. 0.82%, OR: 2.505; 95% CI: 0.261 to 8.689, P = 0.652) and any revascularization (12.76% vs. 9.67%, OR: 1.256; 95% CI: 0.747 to 2.111, P = 0.738) were similar between groups. Conclusions: CAC increased the incidence of TLF and TLR without a substantial increase in the risk of MACE, cardiac death, MI, or any revascularization in patients treated with DCB-only angioplasty during the 3-year follow-up.